4(k+5)=2(9k-2)

Simple and best practice solution for 4(k+5)=2(9k-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(k+5)=2(9k-2) equation:


Simplifying
4(k + 5) = 2(9k + -2)

Reorder the terms:
4(5 + k) = 2(9k + -2)
(5 * 4 + k * 4) = 2(9k + -2)
(20 + 4k) = 2(9k + -2)

Reorder the terms:
20 + 4k = 2(-2 + 9k)
20 + 4k = (-2 * 2 + 9k * 2)
20 + 4k = (-4 + 18k)

Solving
20 + 4k = -4 + 18k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-18k' to each side of the equation.
20 + 4k + -18k = -4 + 18k + -18k

Combine like terms: 4k + -18k = -14k
20 + -14k = -4 + 18k + -18k

Combine like terms: 18k + -18k = 0
20 + -14k = -4 + 0
20 + -14k = -4

Add '-20' to each side of the equation.
20 + -20 + -14k = -4 + -20

Combine like terms: 20 + -20 = 0
0 + -14k = -4 + -20
-14k = -4 + -20

Combine like terms: -4 + -20 = -24
-14k = -24

Divide each side by '-14'.
k = 1.714285714

Simplifying
k = 1.714285714

See similar equations:

| 24xy+6y=0 | | 9n-4n=4n+2n+7 | | 2(8n+6)=-3+n | | 5a-2b=8 | | 3c+2(4)=2 | | 21(7-y)+4=-4 | | 2(x-3)+2X=-14 | | 7-3(5-3v)-8=67 | | 6c=c | | x-6-26=7(x-26) | | Y+7-2=-5 | | x-6+26=7(x+26) | | 8(3B+5)+2= | | X^4-10*X^2-3*X+25=0 | | 5n-2n=9 | | 14d-43=-13-7d | | 70+4y=130 | | -4x+20=-4-x | | 2(5a+6)=2(3a+8) | | -2(4b+3)=-8b-7 | | 7(8+9C)= | | 50+4y=130 | | 2(4-1.3x)-4.1x=0.5 | | 6-9x+10c^2= | | -266=-7(8m-2) | | 4x+5=-x+8+5x-3 | | 3f+g=-14 | | x-6+7=26(x+7) | | 7*8-6+3=47 | | S+k+m=180 | | -2x(x+4)+6=-3 | | (3a+7)+(2a-6)=(-9) |

Equations solver categories